2019
DOI: 10.31219/osf.io/za5h8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sparking Creativity with Robots: A Design Perspective

Abstract: We present the design and evaluation process of a robot aimed at stimulating creativity in humans in a collaborative drawing-oriented task. Collaboration towards a common goal is known to be one of the most influential factors for creativity nourishing. The social robot acted as a collaborative peer in a drawing activity, taking turns with the human, to complete their drawing. In each turn, both "artists" (the robot and the human) draw something new until they achieved their final drawing. The goal was to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Finally, while this work evaluates the role of the robot’s creativity fostering behaviors, it does not evaluate the benefits of embodiment over other non-embodied agents such as computers or voice agents. Previous research has found that adults did not show significant gains in creativity merely in the presence of a social robot ( Alves-Oliveira et al, 2019 ). In future work, we aim to study the combined effect of embodiment and creativity scaffolding behaviors by running a 2 × 2 study ({embodied, non-embodied}×{scaffolding, non-scaffolding}) ( Devasia et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Finally, while this work evaluates the role of the robot’s creativity fostering behaviors, it does not evaluate the benefits of embodiment over other non-embodied agents such as computers or voice agents. Previous research has found that adults did not show significant gains in creativity merely in the presence of a social robot ( Alves-Oliveira et al, 2019 ). In future work, we aim to study the combined effect of embodiment and creativity scaffolding behaviors by running a 2 × 2 study ({embodied, non-embodied}×{scaffolding, non-scaffolding}) ( Devasia et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
“…Previous work has demonstrated how social robots can influence children’s learning behaviors such as curiosity, growth mindset, and empathy through social emulation ( Gordon et al, 2015 ; Park et al, 2017 ). Notably, the presence of a social robot can also affect adults’ creativity ( Kahn et al, 2016 ; Alves-Oliveira et al, 2019 ). In this work, we explore how social robots can foster creativity in young children through collaborative, playful interactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the examples we saw in robotics use interaction patterns to support users' creativity. Robots adopt the role of either a supportive agent that facilitates the user's creativity (Elgarf et al, 2021;Alves-Oliveira et al, 2019) or a creative peer that is collaborating with the user on a creative task (Law et al, 2019;Lin et al, 2020;Hu et al, 2021). In that sense, all of the examples put creative thinking of the user as an aim of the robot.…”
Section: Introductionmentioning
confidence: 99%